Number of reflux episodes on pH-impedance monitoring associates with improved symptom outcome and treatment satisfaction in gastro-oesophageal reflux disease (GERD) patients with regurgitation. Issue 3 (28th May 2020) - Rogers, Benjamin D; Valdovinos, Luis R; Crowell, Michael D; Bell, Reginald; Vela, Marcelo F; Gyawali, C Prakash
Abstract : Objective: Number of reflux episodes, an adjunctive metric on pH-impedance monitoring, is incompletely studied. We aimed to determine if number of reflux episodes associates with therapeutic outcome in regurgitation predominant gastro-oesophageal reflux disease (GERD). Design: We performed post hoc analysis of postintervention pH-impedance data from adult patients with moderate/severe regurgitation despite QD proton pump inhibitor (PPI), randomised to either two times a day PPI or magnetic sphincter augmentation (MSA) in 2:1 allocation. After 6 and 12 months, symptom response was defined by improvement in Foregut Symptom Questionnaire (FSQ) regurgitation score to none or minimal, ≥50% reduction in GERD health-related quality of life (HRQL) score and satisfaction with therapy. Univariate and multivariate analyses were performed to determine predictors of symptom improvement. Results: Of 152 randomised patients, 123 (age 46.9±1.2 year, 43% female) had complete data. Symptom and satisfaction scores significantly improved after MSA compared with two times a day PPI. Both acid exposure time (13.4%±0.7% to 1.3±0.2%, p<0.001) and reflux episodes (86±4 to 48±4, p<0.001) declined with therapy. Reduction to <40 reflux episodes was significantly more frequent in those with symptom response by FSQ regurgitation score, GERD HRQL score and satisfaction with therapy (p≤0.03 for each); <35 episodes performed better on receiver operating characteristic analysis. On multivariate analysis, improvement in regurgitation score remained independently predictive of satisfaction with therapy (p<0.001 for each). In patients crossing over to MSA, >80 episodes pretreatment predicted improvement. Conclusions: Reduction of reflux episodes on pH-impedance to physiological levels associates with improved outcomes, while pathological levels predict improvement with MSA in regurgitation predominant GERD. Trail registration number: ClinicalTrials.gov: NCT02505945 .